Islam & problem gender. Telaah kepemimpinan wanita dalam perspektif tarjih Muhammadiyah - [Tidak Terdaftar] (Aditya Media, 2000)
Islam & problem gender. Telaah kepemimpinan wanita dalam perspektif ...